The Antibacterial Effects of Clove Oil and Aqueous Clove Extract Against Staphylococcus Aureus - Lazam Abraik; Faeza Mharb; Hakma Aboamoud (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to evaluate and compare the antibacterial effects of clove oil and aqueous clove extract on Staphylococcus aureus. Using the agar well diffusion method, different concentrations of clove oil (100%, 50%, 25%) and aqueous extract (100%, 50%, 25%) were tested. A standard antibiotic (Vancomycin) and sterile water served as positive and negative controls, respectively. The results demonstrated that clove oil exhibited a strong inhibitory effect, especially at 100% concentration, while the aqueous extract showed limited antibacterial activity. Statistical analysis using one-way ANOVA indicated significant differences between treatment groups (p < 0.05). These findings suggest that clove oil, due to its high eugenol content, can be a potent natural antibacterial agent against S. aureus.